The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2nr01448c
|View full text |Cite
|
Sign up to set email alerts
|

Boosting photocatalytic CO2 reduction via Schottky junction with ZnCr layered double hydroxide nanoflakes aggregated on 2D Ti3C2Tx cocatalyst

Abstract: Designing efficient photocatalysts is vital for the photoreduction of CO2 to produce solar fuels, helping to alleviate issues of fossil fuel depletion and global warming. In this work, a novel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Other than that, when Co–Co layered double hydroxide (LDH) was coupled with Ti 3 C 2 T x nanosheets to form Co–Co-LDH/TNS nanoarrays, Chen et al posed a massive spike in the CO 2 -to-CO evolving rate (12 500 μmol g −1 h −1 ) with the aid of Ru-based photosensitizers, which had outstanding stability (>25 h, 5 cycles) and a high AQY (0.92%). 183 Furthermore, other works using LDH such as 2D/2D NiAl-LDH/Ti 3 C 2 by Shi et al 184 and 2D/2D ZnCr-LDH/Ti 3 C 2 T x by Zhou et al 47 were found to divulge superb CO 2 RR capability with CO selectivities of 92% and 86%, respectively, which were much higher than those in the aforementioned works. All the robust performances from LDH-incorporated systems are largely attributed to the compositional flexibility of LDHs, which is the result of the universal applicability of cations in layers and anions in the interlayer, granting them to expeditiously cull the appropriate cations and anions for a tailored electronic structure and active centers for specific photocatalytic reactions.…”
Section: Mxenes In the Catalytic Co2 Reduction Reactionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other than that, when Co–Co layered double hydroxide (LDH) was coupled with Ti 3 C 2 T x nanosheets to form Co–Co-LDH/TNS nanoarrays, Chen et al posed a massive spike in the CO 2 -to-CO evolving rate (12 500 μmol g −1 h −1 ) with the aid of Ru-based photosensitizers, which had outstanding stability (>25 h, 5 cycles) and a high AQY (0.92%). 183 Furthermore, other works using LDH such as 2D/2D NiAl-LDH/Ti 3 C 2 by Shi et al 184 and 2D/2D ZnCr-LDH/Ti 3 C 2 T x by Zhou et al 47 were found to divulge superb CO 2 RR capability with CO selectivities of 92% and 86%, respectively, which were much higher than those in the aforementioned works. All the robust performances from LDH-incorporated systems are largely attributed to the compositional flexibility of LDHs, which is the result of the universal applicability of cations in layers and anions in the interlayer, granting them to expeditiously cull the appropriate cations and anions for a tailored electronic structure and active centers for specific photocatalytic reactions.…”
Section: Mxenes In the Catalytic Co2 Reduction Reactionmentioning
confidence: 84%
“…1a and b). There are more studies showing the feasibility of MXene-based coupled heterostructures in the CO 2 RR such as V s -CdS/Ti 3 C 2 , 12 SnO 2 /MXene, 44 Ru/Ti 3 CN/TiO 2 , 45 Cu/Ti 3 C 2 T x /g-C 3 N 4 , 46 ZnCr-LDH/Ti 3 C 2 T x 47 and Cs 2 AgBiBr 6 /Ti 3 C 2 T x . 48 Therefore, to fully understand the structure–activity relationship of MXenes in heterojunctions, the necessity of a review that summarizes the recent studies is in urge.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the NiS/BiVO 4 photocatalyst under light irradiation produces more ˙O 2 − than BiVO 4 , which indicates that the reductive activity of O 2 adsorbed on the NiS/BiVO 4 surface obtains a remarkably higher enhancement than that of BiVO 4 . 46,47 Moreover, the rapid depletion of photogenerated holes from BiVO 4 also contributes to the O 2 reduction to H 2 O 2 . Thus, photocatalytic degradation experiment is further used to verify that the selectively modified NiS cocatalyst can improve the interfacial catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…45 In the case of ZnCr-LDH/Ti 3 C 2 T x heterostructures, the Fermi energy of ZnCr-LDH is higher than that of Ti 3 C 2 T x ; hence the electrons from ZnCr-LDH are driven to Ti 3 C 2 T x to equilibrate the Fermi energy between them. 47 During photocatalysis, the energy band of ZnCr-LDH bends upwards, producing a Schottky barrier. Under light irradiation, the photogenerated electrons migrate along the Schottky junction to the MXene, achieving effective electron separation.…”
Section: Applications Of Mxene/ldh Hybridsmentioning
confidence: 99%
“…More importantly, MXene/LDH hybrids with weak van der Waals (vdW) interactions can preserve the individual intrinsic characteristics of each 2D layered material while exposing an immense contact interface between them, which is highly benecial for energy storage and electrocatalysis applications. As a result of the synergy from the heterointerface, remarkable advances have appeared in the elds of supercapacitors (hybrid, asymmetric, and all solid-state), 27,[34][35][36][37] batteries (Li-ion and metal-air), electrochemical water splitting, [38][39][40][41][42][43] photocatalytic/electrochemical CO 2 reduction reaction (CO 2 RR), [44][45][46][47] sensors (gas and glucose), 48,49 anti-corrosion, ame retardancy, 28 and electromagnetic wave absorbers. 50 Scheme 1 summarizes the properties, problems, and prospects of MXenes and LDHs.…”
Section: Introductionmentioning
confidence: 99%